2015
DOI: 10.1039/c5ob00469a
|View full text |Cite
|
Sign up to set email alerts
|

An interactive database to explore herbicide physicochemical properties

Abstract: Herbicides are an essential tool not only in weed management, but also in conservation tillage approaches to cropping. The first commercial herbicides were released in the 1940s and hundreds more since then, although genetic resistance to them is an issue. Here, we review the experimental and estimated physicochemical properties of 334 successful herbicidal compounds and make available a dynamic electronic database containing detailed analyses of the main chemical properties for herbicides and which adopts the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 24 publications
0
52
0
2
Order By: Relevance
“…Removing the furanyl moiety and installing polar groups,asin 16 and 17,also reduced potency. Interestingly,motifs such as 5,9,14,18 where the size of the side chain was similar, but the furanyl moiety modified to include more flexibility and potential H-bond forming groups,aloss of potencyw as also observed. Modification of the 4-position of the carboxamide functionality also affected herbicidal activity.Whenthe amide was replaced with as imple methyl group 1,a ne ster functionality as in 3,o rp arent acid 2,h erbicidal activity was significantly impaired.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Removing the furanyl moiety and installing polar groups,asin 16 and 17,also reduced potency. Interestingly,motifs such as 5,9,14,18 where the size of the side chain was similar, but the furanyl moiety modified to include more flexibility and potential H-bond forming groups,aloss of potencyw as also observed. Modification of the 4-position of the carboxamide functionality also affected herbicidal activity.Whenthe amide was replaced with as imple methyl group 1,a ne ster functionality as in 3,o rp arent acid 2,h erbicidal activity was significantly impaired.…”
mentioning
confidence: 89%
“…To refine the number of hit compounds to test on soil, the physicochemical properties of the eleven hit compounds selected from the plate assay were compared to those in an interactive database of physicochemical properties of 334 commercial herbicides ( Figure 1B;s ee also Figure S1 and Table S1 in the Supporting Information). [18] Using cluster analyses where two physicochemical properties (e.g.L og S, Log P,number of rotatable bonds) can be compared as well as direct comparison of the physicochemical properties against the average observed for known herbicides,t he hits were narrowed down to five compounds (Hits B, D, E, F, and G) and these were taken forward for more rigorous analysis of herbicidal activity using soil-grown A. thaliana. Seeds or seedlings were treated with arange of concentrations of Hits B, D, E, F, and G( 0-400 mg L À1 )t oe xamine the compounds herbicidal activity when applied pre-or post-emergence-an important consideration in herbicide development.…”
mentioning
confidence: 99%
“…[2] In spite of this,t he synthetic toolkit that currently dominates molecular discovery is remarkably narrow, [3] which not only contributes to our collective unsystematic and uneven exploration of chemical space, [4] but can also drive discovery away from optimal property space! [5][6][7][8][9][10] In many cases, compounds that would provide good starting points for discovery have substantially different properties to those of final optimized [1,2] functional molecules,a nd specific attributes of screening compounds, [5] fragments, [6] building blocks, [7] and robust reactions [8] ford rug discovery applications have been clearly described. [5][6][7][8][9][10] In many cases, compounds that would provide good starting points for discovery have substantially different properties to those of final optimized [1,2] functional molecules,a nd specific attributes of screening compounds, [5] fragments, [6] building blocks, [7] and robust reactions [8] ford rug discovery applications have been clearly described.…”
Section: Introductionmentioning
confidence: 99%
“…Guidelines have been formulated to help steer chemists towards property space that is relevant to particular classes of functional small molecules,i ncluding drugs [1] and agrochemicals. [2] In spite of this,t he synthetic toolkit that currently dominates molecular discovery is remarkably narrow, [3] which not only contributes to our collective unsystematic and uneven exploration of chemical space, [4] but can also drive discovery away from optimal property space! [3a] Recent high-profile articles authored by industrial scientists have challenged the academic community to develop innovative synthetic methods that align with future discovery needs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a recent compilation of herbicides revealed that 90% of herbicides' active ingredients contain an aromatic ring as well. 20 Synthesis of aryl compounds is primarily accomplished by aromatic substitution reactions such as classical nucleophilic aromatic substitution (SNAr) 21 and contemporary transition metal catalysis. 22 Due to the high cost and technical difficulty of metal-catalyzed arylations, research efforts have been focused on metal-free arylations which are severely limited by their reaction mechanism (i.e., SNAr).…”
Section: Relevancementioning
confidence: 99%